MIDWIVES' PERCEPTIONS OF PREECLAMPSIA SCREENING - Febronia Martina Dua Lehang; Aditiawarman; Ivon Diah Wittiarika; Linda Dewanti (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Preeclampsia-related maternal mortality is a persistent issue globally, including in Indonesia. The International Federation of Gynecology and Obstetrics (FIGO) recommends universal preeclampsia screening in obstetric services. In Indonesia's NTT Province, pregnant women are screened based on guidelines in the MCH book. Sikka Regency mandates midwives to use the KSPR and MCH manuals for risk factor screening In 2022, 154 out of 9,685 screened pregnant women exhibited signs of preeclampsia risk factors. Despite the reduction in maternal deaths in Sikka Regency, the number of deaths directly linked to preeclampsia increased from one in 2021 to four in 2022. Notably, at Watubaing Public Health Center, two cases of maternal death were specifically attributed to preeclampsia. This underscores a significant gap in midwives' perceptions and clinical practices, elevating maternal mortality risk. This study explores midwives' perceptions of preeclampsia screening. Method: Qualitative research with a phenomenological approach at Watubaing Public Health Center involved three informants selected through purposive sampling, meeting the inclusion criteria. Data collection, conducted from April to July 2023, comprised in-depth semi-structured interviews that were subsequently analyzed thematically. Results: Midwives' expressed divergent opinions on preeclampsia screening, yet a consensus prevailed on its crucial importance. Conclusion: Midwives' perceptions of preeclampsia screening in ANC services are significantly shaped by internal and external factors, including knowledge and experience.